Random Coefficients and Unbalanced Panels: An Application on Data from Norwegian Chemical Plants - Erik Biørn; Kjersti-Gro Lindquist (Statistics Norway, Research Department, 1998)
A framework for analyzing substitution and scale properties, and technical change from plant-level panel data is presented. Focus is on comparing the constant and random coefficient specification of the substitution and scale parameters and investigating the potential variation of the parameters across firms. Characteristics of the model framework are (i) an equation system consisting of a three-factor translog cost function and the corresponding cost-share equations, (ii) random firm specific heterogeneity in coefficients, and (iii) a Maximum Likelihood procedure allowing for unbalanced panel data. The empirical results, based on data from Norwegian chemical plants, indicate substantial firm specific heterogeneity in substitution and scale properties.
Keywords: C33; D21; D24; L65; 330; Panel Data. Random Coefficients. Unbalanced Data. Heterogeneity. Production technology